Studies on CRMP2 SUMOylation–deficient transgenic mice identify sex-specific Nav1.7 regulation in the pathogenesis of chronic neuropathic pain. Issue 11 (November 2020) - Moutal, Aubin; Cai, Song; Yu, Jie; Stratton, Harrison J.; Chefdeville, Aude; Gomez, Kimberly; Ran, Dongzhi; Madura, Cynthia L.; Boinon, Lisa; Soto, Maira; Zhou, Yuan; Shan, Zhiming; et al.
Abstract : Abstract: The sodium channel Nav 1.7 is a master regulator of nociceptive input into the central nervous system. Mutations in this channel can result in painful conditions and produce insensitivity to pain. Despite being recognized as a "poster child" for nociceptive signaling and human pain, targeting Nav 1.7 has not yet produced a clinical drug. Recent work has illuminated the Nav 1.7 interactome, offering insights into the regulation of these channels and identifying potentially new druggable targets. Among the regulators of Nav 1.7 is the cytosolic collapsin response mediator protein 2 (CRMP2). CRMP2, modified at lysine 374 (K374) by addition of a small ubiquitin-like modifier (SUMO), bound Nav 1.7 to regulate its membrane localization and function. Corollary to this, preventing CRMP2 SUMOylation was sufficient to reverse mechanical allodynia in rats with neuropathic pain. Notably, loss of CRMP2 SUMOylation did not compromise other innate functions of CRMP2. To further elucidate the in vivo role of CRMP2 SUMOylation in pain, we generated CRMP2 K374A knock-in (CRMP2 K374A/K374A ) mice in which Lys374 was replaced with Ala. CRMP2 K374A/K374A mice had reduced Nav 1.7 membrane localization and function in female, but not male, sensory neurons. Behavioral appraisal of CRMP2 K374A/K374A mice demonstrated no changes in depressive or repetitive, compulsive-like behaviors and a decrease in noxious thermal sensitivity. No changes were observed in CRMP2 K374A/K374A mice to inflammatory, acute, or visceral pain. By contrast, in a neuropathic model, CRMP2 K374A/K374A mice failed to develop persistent mechanical allodynia. Our study suggests that CRMP2 SUMOylation–dependent control of peripheral Nav 1.7 is a hallmark of chronic, but not physiological, neuropathic pain. Abstract : Supplemental Digital Content is Available in the Text.CRMP2 SUMOylation modulates peripheral Nav 1.7 channels to control chronic, but not physiological, neuropathic pain.